Study on the Applicable Room Size Dimension of Stratum Ventilation for Heating Based on Multi-Criteria Analytic Hierarchy Process-Entropy Weight Model - Yanhui Mao; Honglei Xie; Xinlu Zhang; Fumin Hou; Miantong Wang (Buildings, 2023)
With the implementation of clean heating and the outbreak of COVID-19, stratum ventilation with both energy-saving and healthy indoor environments has become a research hotspot. Room size dimension is one of the critical factors affecting the air distribution, thermal comfort, and ventilation performance of space heating, which is still a research blank at present. This study determined the applicable room size dimension of stratum ventilation for space heating by using a multi-criteria analytic hierarchy process-entropy weight (AHP-EW) model. A computational fluid dynamics (CFD) simulation verified by experiments was conducted. To investigate the ventilation performance of different room sizes in energy utilization and thermal comfort, airflow distribution, ventilation efficiency (Et), dimensionless temperature, effective ventilation temperature (EDT), air distribution performance index (ADPI), and predicted mean vote (PMV) were calculated. The multi-criteria AHP-EW method is used to evaluate every case comprehensively. The results show that the maximum room size obtained by multi-criteria APH-EW is 6 m, and considering the single criteria, the suitable height for stratum ventilation for heating is below 5.7 m. The data obtained in this paper can be used as a reference for further study on the application of stratum ventilation and heating in the future.